The Relevance of Ibn Sina's Philosophy of Education to the Development of MI Curriculum in the Merdeka Belajar Era - Hamima S Toku; Sukardi Abbas; Sahjad M Aksan; Elfira Mahmud (Manunggal Halim Jaya, 2026)
This study explores the relevance of Ibn Sina's educational philosophy to the development of the Madrasah Ibtidaiyah curriculum in the Merdeka Belajar era. Using a qualitative approach with a literature review and field study design, data were collected through the analysis of Ibn Sina's works, Merdeka Curriculum policy documents, interviews with 20 madrasah practitioners, and focus group discussions. The results of the study indicate five main philosophical convergences: a student-centered learning paradigm, differentiated learning, a holistic approach, enjoyable learning, and character formation. Ibn Sina's philosophy provides an epistemological foundation for integrating Islamic values with modern pedagogy, a development-stage-based learning framework, and universal pedagogical principles. The integration model is formulated in five dimensions: vision-goal, curriculum design, learning strategies, holistic assessment, and educator development. Implementation challenges include educator competence, learning resources and mindset resistance. A comprehensive strategy is recommended to transform the MI curriculum to be responsive to the 21st century while being grounded in authentic Islamic values.